Modality in the Selected Continents Airlines’ COVID-19 Instructions: A Corpus-Based Study - Rabia Naz; Dr. Rasib Mahmood; Aqsa Atta (Journal of Management Practices, Humanities and Social Sciences, 2022)
Modal verbs are generally critical in expressing an opinion and assist in the depiction of future events. This work represents and analyzes the function and frequency of modal verbs used in airlines' guidelines during the COVID-19 pandemic. By employing a mixed-methods approach, the corpus was analyzed using Antconc 3.5.8.0. The data were categorized into six components, including ability, possibility, permission, prediction, acknowledgment, and obligation. The findings show that in African and Asian Airlines’ instructions, modal verbs are used to share their opinion related to the instructions for the future. Also, findings reveal that ‘can' and ‘will’ are used to predict possible events. Furthermore, findings show that in European airlines' instructions, the obligatory modal verb ‘must’ is used to enforce their instruction for better comprehension. Additionally, findings also show that Asian writers are more aligned towards using modal verbs than Middle East writers who are least concerned about using modal verbs. The most recurring modal verb used by the writers is their predictive modal verb ‘will’ and the obligatory modal verb ‘must.' This study implies that readers should be conscious of the writer's stance marking since it may affect the mind and exploit ideas.